Contraception in perimenopause: a review of fecundity, fertility, and feasibility of contraceptives - Devalla, Anusha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Menopausal transition warrants effective contraception despite reduced fecundity and fertility. The associated maternal and perinatal morbidities and mortality in women after 40 years has prompted women to choose safe and reliable contraceptives. Although the majority of women globally opt for sterilization; however, the observed trends in the last decade have seen an increase in the use of Long-acting reversible contraceptives. Combined hormonal contraceptives have been disrepute traditionally but the current literature remarks the use of CHC in selected populations. A literature search was conducted till December 2023 using the PubMed, Embase, SCOPUS databases and recommendations by various organizations using related search terms. This review highlights the various contraceptive options currently dispensed in the armamentarium for women above 40 years. The aim is to focus on the associated co-morbidities that can affect the contraceptive choices in this group and the contraceptive effects on the menopausal symptoms. This would guide the clinicians in prescribing the methods considering the complex requirements.